Transformational Leadership and Knowledge Management Impact on Organization Performance: A Systematic Review - Tan Hadi; Alexander Batara Marpaung (CV. Ridwan Publisher, 2023)
A leader is a frontrunner who will bring an organization to sail to its desires. In wearing out its functions a leader will normally use the management style/version this is believed to be the most perfect to support his achievement. Transformational leadership is leadership that gives freedom to the enterprise to offer thoughts for the progress of the employer, lets in subordinates to see troubles from special views, enables adapt to the converting environment, and improves the effectiveness of Human aid control in numerous sectors of the business enterprise. The influence of transformational management on organizational overall performance through expertise control has been studied in various research. This journal is the end result of systematic opinions from several journals on the influence of transformational management and information control on organizational overall performance. From the consequences of the literature search, five journals related to transformational leadership and know-how management effect on organizational overall performance had been determined. The consequences of the systematic evaluation show that the transformational management fashion and information management has a positive influence on enterprise performance, both at once and in a roundabout way.